The Effect of Active Chitosan Films Containing Bacterial Cellulose Nanofiber and ZnO Nanoparticles on the Shelf Life of Loaf Bread - Mehrasa Bakouei; Jalal Sadeghizadeh Yazdi; Mohammad Hasan Ehrampoush; Mahdieh Salari; Farzan Madadizadeh (Journal of Food Quality)
Due to the disadvantages of synthetic packaging materials such as migration, environmental pollution, lack of easy recycling, and high production costs, natural polymers have received much attention as safe and biodegradable alternatives to plastics. The aim of this study was to investigate the effect of the active film of chitosan (CH) containing bacterial cellulose nanofiber (BCNF) and ZnO nanoparticles (ZnO NPCs) on the shelf life of loaf bread (toast, baguette, and sandwich-type bread). The results showed that ZnO NPCs significantly reduced the thickness and water vapor permeability (WVP) and increased the opacity of films p<0.05. CH-BCNF-ZnO 2% NPCs film had the lowest thickness and WVP and the highest opacity. Differential scanning calorimetric (DSC), thermal gravimetry analysis (TGA), and derivative thermogravimetry (DTG) showed that ZnO NPCs increased the thermal stability of chitosan films. CH-BCNF-ZnO 1% NPCs had the highest melting point (148.66°C) and melting enthalpy (ΔHm). Scanning electron microscopy (SEM) images showed the good distribution of ZnO NPCs in the chitosan film. The higher concentrations of ZnO NPCs formed aggregates in the polymer. ZnO NPCs had a significant effect on the physicochemical properties of bread. The highest moisture content and water activity aw were observed in CH-BCNF-ZnO 2% toast and control toast, respectively. CH toast showed high ash and insoluble ash. CH baguettes and control baguettes showed the highest pH. As the ZnO NPCs concentration increased, the nanoparticle migration increased. The highest migration was observed in CH-BCNF-ZnO 2% baguette. The highest and lowest hardness was observed in CH-BCNF-ZnO NPCs 2% baguette and CH-BCNF- ZnO NPCs 1% toast bread, respectively. Composite films decreased the microbial population in all bread samples except sandwich-type bread. It can be concluded that BCNF and ZnO NPCs improve the physical properties of chitosan film and can be suggested as active packaging in bread.